On the road to trade union dialogue: management of social conflicts related to road freight transport (Peru, 2019-2022) - Chumpitazi Ramírez, Julio Eduardo (2024)
Social conflict related to road freight transporters is few in number. However, its effects in terms of economic losses and violations of rights are considerable. Between 2019 and 2022, the Ministry of Transport and Communications addressed these conflicts through union dialogue. For this reason, it is worth investigating the operation of this management mechanism. For this purpose, a qualitative emerging grounded theory study was designed. Specifically, a documentary investigation was carried out on the information produced by the ministry, the Ombudsman's Office and the media. It was found that the interaction with freight transport unions produced in the public sphere allowed State agents to implement the dialogue management strategy with a cooperative model and competitive negotiation tactics focused on dissolving protest actions. It is concluded that the institutionalization of this process consolidated the union dialogue and reformulated the dynamics and relationships between the agents of the Peruvian State and the freight transport unions. In this way, union dialogue opened the door to a public sphere that is the arena for disputes and consensus of a more political nature. This could indicate a process of politicization of the economic agents of road freight transport.